ASSESSING THE NIGERIA POLICE FORCE’S STRATEGIES AGAINST ARMED BANDITRY IN KATSINA STATE (2017-2022) - Idris, Abdulrahman; Maliki, Ahmadu Seidu (African Journal of Social and Behavioural Sciences, 2025)
The study examined the strategies of the Nigeria Police Force (NPF) in the fight against armed banditry in Katsina State, Nigeria, from 2017 to 2022. The following research objectives guided the study: understand the strategies adopted by the NPF in the fight against armed banditry and investigate the frequently used modus operandi by the NPF to fight armed banditry in the State. The study was anchored on the Situational Crime Prevention Theory that Ronal Clark propounded. Primary and secondary sources of data were sourced from the 10 frontline Local Government Areas (LGAs) affected by armed banditry in the State. A multi-stage cluster sampling method comprised of cluster sampling, stratified sampling and simple random sampling techniques was used because the study area was large in size while the population was scattered across the State. A sample size of 700 questionnaires was administered to the study’s respondents. Additionally, 22 Key Informant Interviews (KIIs) were purposively conducted with police officers, vigilantes, male and female residents, village heads, youth leaders, arrested bandits held in police custody, and detained alleged informants of bandits held in police custody. Findings revealed that NPF in the State have carried out a sustained campaign against corruption among its personnel, deployed Operation Puff Adder Teams, personnel from the Intelligence Response Teams (IRT) and Force Intelligence Bureau (FIB) as strategies against armed banditry in the State. The study also revealed that other strategies adopted by the police against armed banditry in the State were the deployment of personnel of the Police Mobile Force (PMF) and Special Tactical Forces (STF) against armed bandits in the State. The study further revealed that the frequently used strategy by the NPF to fight armed banditry in the State was the use of personnel from the PMF and the deployment of Operation Puff Adder teams. It was recommended that the Federal Government of Nigeria (FGN) procure modern technological and logistical tools for the NPF to enable the police to commence the use of information and communication technology gadgets and armoured personnel Carriers (APCs) as part of its improved multifaceted initiatives in the fight against armed banditry in the State. Also, the FGN, which is the proprietor of both NPF and the Nigerian Military, must create a deliberate policy for regular joint police and military operations against armed banditry to foster inter-agency collaboration in the State.